The Identification of Potential Rafting Tourism Products in Citepok Village, Sumedang Regency, West Java Province - Satriani Siti Nurlaila; Eko Susanto; Kurnia Fajar Afgani (Politeknik Negeri Bandung, 2021)
Sumedang Regency is a natural, historical and cultural tourist destination. There are still many tourism potentials that have not been built and developed optimally. The natural resources of the Sumedang regency in rivers can be used as unique interest tourism resources, namely rafting. These resources can support the vision and mission of tourism in Sumedang regency who want to build their territory as a natural, historical and cultural tourism destination and special interests that are well known both nationally and internationally. To find out the potential of research conducted with the title Of Analysis of Tourism Product Potential in Sumedang Regency. The method of research conducted is qualitative. Data collection methods include observation, interviews, documentation and library studies. While the data analysis techniques used are descriptive. The results showed that, especially in the Cipeles river, Citepok village could develop rafting tourism products. The unique attraction of the Cipeles river is that the river flow is in grade 2 rafting path and a line flanked by beautiful rock cliffs. Tourist facilities such as inns and restaurants are adequate. Additional services such as financial, security, health and rafting services are available around Citepok village.